Ответ нейросети
08 May 2024 09:08
1.
2.
3. (а - 10)^2 - (а - 5)(a + 5) = a^2 - 20a + 100 - (a^2 - 25) = a^2 - 20a + 100 - a^2 + 25 = -20a + 125
4. (2x - 7)(x + 1) + 3(4x - 1)(4x + 1) = 2(5x - 2)^2 - 53 Expanding and simplifying this equation will lead to the solution for x.
5. (3a + 1)^2 - (a + 6)^2 = (3a + 1 + a + 6)(3a + 1 - a - 6) = (4a + 7)(2a - 5)
6. (2 - x)(2 + x)(4 + x^2) + (6 - x^2)^2 can be simplified by applying the values of x. For x = -1, evaluate the expression to find its value.
7. To prove that the expression 12 - 18x + 84 is positive for all values of x, we can take the derivative of the expression and analyze its sign.
Понравился ответ?
40
2
Похожие вопросы
Задавай вопросы искуcственному интеллекту текстом или фотографиями в приложении на iPhone или Android
ПО распространяется в виде интернет-сервиса, специальные действия по установке ПО на стороне пользователя не требуются